Healthy Living Behavior, Life Satisfaction and Social Support In Productive Age Individuals - Hermiana Vereswati; Sri Widyawati; Martha Kurnia Asih (Philanthropy: Journal of Psychology, 2024)
Abstract. Indonesia will face an era of demographic bonus and the health of the productive age is valuable capital for accelerating development. The aim of the research is to determine the effect of healthy behavior on life satisfaction with social support as an intervening variable. Research population of individuals of productive age in Indonesia. The research sample was individuals aged 21 to 45 years who lived in Semarang, Solo, Jakarta, Surabaya and were not on a medical diet. The sampling technique is accidental sampling using Google Form. The data analysis technique uses intervening variable regression with the path analysis method with the SPSS application. The results of data analysis from 245 respondents showed that there was a significant direct influence of healthy living behavior on life satisfaction of 0.182 and there was a significant indirect influence of healthy living behavior on life satisfaction through social support of 0.285. Healthy living behavior must be carried out continuously to support productivity so that it contributes to life satisfaction in the future.Keywords: Healthy Living Behavior; Social Support; Life Satisfaction